First record of two Leptothecata medusae (Cnidaria, Hydrozoa) in Colombia with annotations on their distribution and ecology - Jorge Llorente-Vega; Cristina Cedeño-Posso; Jorge Quirós-Rodríguez (Biodiversity Data Journal)
Hydromedusae are a group of planktonic cnidarians that represent the medusoid phase in the life cycle of most members of the class Hydrozoa, whose primary function is to produce and release gametes. These organisms are generally small and translucent, with slight pigmentation, except for those that inhabit great depths and exhibit the typical body shape of a jellyfish. In Colombia, studies on this group are limited due to the scarcity of updated taxonomic information and the small number of expert scientists. The most recent inventory records 71 species in the waters of the Pacific and Atlantic Oceans.In this study, we report for the first time the presence of Eucheilota duodecimalis and Eutonina scintillans in Colombia, based on 28 zooplankton samples collected from seven stations between February and May 2024, using horizontal tows with a simple conical zooplankton net. Our research emphasises the significance of scientific exploration in new geographic regions and provides valuable data on the distribution and ecology of these species, contributing to a deeper understanding of their population dynamics.